ANALYSIS OF ELEMENTARY SCHOOL CHILDREN'S KINESTHETIC INTELLIGENCE THROUGH TIK TOK SOCIAL MEDIA - A'yunun Nadhirah; Agung Setyawan; Mohammad Usman; Moh Rahbini (Citra Dharma Cindekia, 2022)
This study aims to determine the social media Tik Tok as a supporter of kinesthetic intelligence in elementary school students. In this study, there are several kinesthetic activities in Tik Tok social media to support the development of kinesthetic intelligence in elementary students. The method used in this research is a literature study (Review Study). The results in this study indicate that there are several activities on Tik Tok social media that are carried out by students as supporters of students' kinesthetic intelligence, namely dance, sport, drama and gymnastics. The conclusion of this study is that there are several activities related to kinesthetic intelligence such as dance, sport, drama and gymnastics that can have a positive influence and increase students' knowledge and experience to develop students' kinesthetic intelligence